Satisfaction among early and mid-career dentists in a metropolitan dental hospital in China - Cui X; Dunning DG; An N (Dove Medical Press, 2017)
Xiaoxi Cui,1 David G Dunning,2 Na An3 1College of Dentistry, University of Nebraska Medical Center, Lincoln, NE, USA; 2Department of Oral Biology, College of Dentistry, University of Nebraska Medical Center, Lincoln, NE, USA; 3School of Stomatology, Department of General Dentistry II, Peking University School and Hospital of Stomatology, Beijing, People’s Republic of China Abstract: A growing body of research has examined career satisfaction among dentists using a standardized instrument, dentist satisfaction survey (DSS). This project examined career satisfaction of early to mid-career dentists in China, a population whose career satisfaction, heretofore, has not been studied. This is an especially critical time to examine career satisfaction because of health care reform measures being implemented in China. A culturally sensitive Chinese-language version of the DSS (CDSS) was developed and electronically administered to 367 early and mid-career dentists in a tertiary dental hospital in Beijing, China. One hundred and seventy respondents completed the survey. The average total career score was 123, with a range of 82–157. Data analysis showed some significant differences in total career score and several subscales based on gender, working hours per week, and years in practice. A stepwise regression model revealed that two variables predicted total career score: working hours per week and gender. Stepwise regression also demonstrated that four subscales significantly predicted the overall professional satisfaction subscale score: respect, delivery of care, income and patient relations. Implications of these results are discussed in light of the health care delivery system and dentist career paths in China. Keywords: job satisfaction, career satisfaction, early and mid-career dentists, Chinese health care reform